Postoperative, or pseudophakic, macular edema - I. E. Ioshin (Российский офтальмологический журнал)
Causes of macular edema (ME) occurring on the pseudophakic eye after cataract phacoemulsification, and methods of its diagnosis and prevention are analyzed. As follows from the literature and our own data, the term “pseudophakic ME” better reflects the condition that the term “postoperative ME” as it takes into account the diversity of pathogenetic complications. Accordingly, we propose to include this term into the ICD list.